Proteomic identification of rainbow trout blood plasma proteins and their relationship to seminal plasma proteins. Issue 11 (8th June 2017) - Nynca, Joanna; Arnold, Georg; Fröhlich, Thomas; Ciereszko, Andrzej
Abstract : The characterisation of fish blood proteomes is important for comparative studies of seminal and blood proteins as well as for the analysis of fish immune mechanisms and pathways. In this study, LC‐MS/MS and 2D‐DIGE were applied to compare rainbow trout seminal (SP) and blood plasma (BP) proteomes. The 54 differentially abundant proteins identified in SP are involved in a variety of signalling pathways, including protein ubiquitination, liver X receptor/retinoid X receptor (LXR/RXR) and farnesoid X receptor activation, cell cycle and acute phase signalling. These findings may indicate the prevalence of acute phase signalling pathways in trout SP, and its essential role in protecting spermatozoa and reproductive tissues. Our study provides the first in‐depth analysis of the trout BP proteome, with a total of 119 proteins identified. The major proteins of rainbow trout BP were recognised as acute phase proteins. Analysis of BP proteins indicated that acute phase response signalling, the complement system, liver X receptor/retinoid X receptor and farnesoid X receptor activation and the coagulation system are the top canonical pathways. This study enhances knowledge of the blood origin of trout SP proteins and understanding of fish reproductive biology. Our results provide new insight into blood proteins specifically important for fish physiology and innate immunity. The mass spectrometry data are available via ProteomeXchange with the identifier PXD005988 andhttps://doi.org/10.6019/PXD005988 .